A virtual object manipulation interface for automated assembly programming - Maciejewski, Anthony A., author; Sato, Akihiro, author; IEEE, publisher (Colorado State University. Libraries, 1994)
This work describes the implementation of a novel robotic workcell programming interface that allows an assembly designer to obtain immediate feedback regarding the manufacturability of his design. The interface allows the user to manipulate the three-dimensional CAD/CAM models of the components and "assemble" them into the final product. The computer then analyzes the relevant assembly operations and translates them into low-level commands for the robots in the specific workcell under consideration. This work is motivated by the complexity and time-consuming nature of manually programming flexible assembly cells for the manufacture of different products, particularly when they involve the cooperation of multiple robot manipulators.
Keywords: production engineering computing; graphical user interfaces; CAD/CAM; assembling; robots; robot programming; virtual reality